Evaluation of the Adequacy of the 2010 Revised World Health Organization Recommended Dosages of the First-line Antituberculosis Drugs for Children - Yang, Hongmei (Pediatr Infect Dis J, 2018)
BACKGROUND: The World Health Organization recommended increased dosages of the first-line antituberculosis (anti-TB) drugs for children in 2010. We examined the frequency of and factors associated with low plasma maximum concentration (C(max)) of each drug in children treated with the revised dosages. METHODS: Children on anti-TB therapy for at least 4 weeks underwent pharmacokinetic testing. Plasma C(max) below the lower limit of proposed reference range was considered low. Bivariate and multivariate analyses were used to examine the factors associated with low C(max) of each drug. RESULTS: Of the 100 children, 58% were male, 50% HIV-infected and 49% younger than 5 years old. The median (IQR) C(max) was 5.9 (4.5 – 7.7) μg/mL for isoniazid, 6.5 (4.9 – 8.8) μg/mL for rifampin, 26.0 (21.2 – 33.4) μg/mL for pyrazinamide and 1.7 (0.9 – 2.7) μg/mL for ethambutol. There was a strong correlation between C(max) and AUC(0–8h) for all drugs. Low C(max) occurred in 9/100 (9.0%), 61/100 (61.0%), 17/97 (17.5%), and 60/97 (61.9%) for isoniazid, rifampin, pyrazinamide, and ethambutol, respectively. In addition, 75/97 (77.3%) children had pyrazinamide C(max) < 35 μg/mL. Factors associated with low C(max) were NAT2 metabolizer phenotype status for isoniazid; height, dosage, and HIV coinfection status for rifampin; height for pyrazinamide; and age, dosage and HIV coinfection status for ethambutol. CONCLUSIONS: The high frequency of low rifampin and ethambutol C(max) in our study is consistent with emerging pharmacokinetic data in children treated according to the new WHO recommendations. Higher dosages than currently recommended especially for rifampin may be necessary in children.